2021
DOI: 10.5194/acp-2021-413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpretation of geostationary satellite aerosol optical depth (AOD) over East Asia in relation to fine particulate matter (PM<sub>2.5</sub>): insights from the KORUS-AQ aircraft campaign and seasonality

Abstract: Abstract. Geostationary satellite sensors over East Asia (GOCI and AHI) are now providing continuous mapping of aerosol optical depth (AOD) at 550 nm to improve monitoring of fine particulate matter (PM2.5) air quality. Here we evaluate our understanding of the physical relationships between AOD and PM2.5 over East Asia by using the GEOS-Chem atmospheric chemistry model to simulate observations from multiple sources: 1) the joint NASA-NIER Korea – United States Air Quality aircraft campaign over South Korea (K… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Figure 1 shows the validation example of all MLR models (M1, M2-1, M2-2, M3-1, and M3-2) using AODs retrieved from the MODIS-DT algorithm. Considering the reverse pattern of AOD and PM 2.5 in East Asia [38], the relationship between observed and estimated PM 2.5 from the M1 model (i.e., only AOD is considered) is acceptable, having a linear shape and moderate correlation coefficient (R). However, the slope was 0.15, indicating that the estimated PM 2.5 cannot follow the variation range of observed PM 2.5 .…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the validation example of all MLR models (M1, M2-1, M2-2, M3-1, and M3-2) using AODs retrieved from the MODIS-DT algorithm. Considering the reverse pattern of AOD and PM 2.5 in East Asia [38], the relationship between observed and estimated PM 2.5 from the M1 model (i.e., only AOD is considered) is acceptable, having a linear shape and moderate correlation coefficient (R). However, the slope was 0.15, indicating that the estimated PM 2.5 cannot follow the variation range of observed PM 2.5 .…”
Section: Methodsmentioning
confidence: 99%
“…al., 2006;. Here we use scaled monthly mean GEOS-Chem AODs from a simulation by Zhai et al [2021] for 2016 in East Asia with 0.5 o x 0.625 o resolution. That simulation reported a low mean bias relative to AERONET; we correct this for each year in the study period by using annual mean GOCI AODs on the 6x6 km 2 grid.…”
Section: Aod Gap-fillingmentioning
confidence: 99%
“…The three rapidly decreasing spots on the southern coast are Gwangyang, Sacheon, and Changwon, which house industrial complexes related to the South Korean shipbuilding industry that has recently declined [Jung-a 2016]. AOD and PM2.5 in East Asia tend to have opposite seasonalities driven by boundary layer depth and RH [Zhai et al, 2021]. 2015-2019 but also shows that winter and summer PM2.5 in the region have opposite and roughly equal trends, with winter growing more polluted while summers become cleaner.…”
Section: Pm25 Temporal Trends and Spatial Distributionsmentioning
confidence: 99%
“…term aerosol composition and scattering measurements provided by the IMPROVE network across the continental U.S. (Latimer & Martin, 2019). However, subsequent analysis by Zhai et al (2021) found that this aerosol size underestimated the aerosol mass scattering efficiency and the aerosol extinction coefficients during an aircraft campaign over South Korea (KORUS-AQ). Thus, neglect of aerosol microphysical processes that shape aerosol size distributions can be a significant source of uncertainty in aerosol optical properties in a CTM.…”
Section: Introductionmentioning
confidence: 98%
“…Methods are needed to better represent aerosol size in CCMs or CTMs without a microphysics scheme (referred to as bulk models). These bulk models usually use prescribed relationships to obtain size-resolved aerosol properties (Croft et al, 2005;Karydis et al, 2011;Zhai et al, 2021), which may insufficiently represent the temporal and spatial variation (Kodros & Pierce, 2017). For example, in the GEOS-Chem CTM, a fixed dry aerosol geometric mean radius (Rg) is assumed for organic matter (OM) and sulfate-nitrate-ammonium (SNA), which is based on analysis of long-https://doi.org/10.5194/egusphere-2022-1292 Preprint.…”
Section: Introductionmentioning
confidence: 99%